Attitudes toward migration on the Ecuadorian border - Calvo Rodríguez, Vanessa Mercedes Villarreal Villarreal, Andrés Fabricio Subía Arellano, Diana Carolina Montero Medina, Robin Williams (Opción, 2020)
This study aims to analyze the difference in the attitudes toward migrants that have Ecuadorians living in the border city of Tulcán, compared with the attitude of those who live in the city of Quito. The instrument used was the Scale of Attitudes Towards Immigrants EAPI (by its Spanish acronym) designed by Subía, A.; Arroyo, D.; Montero, D. and Cedeño, X. (2019). Findings show that there is a statistically significant relationship between the variables: level of education, knowledge of the difference between voluntary migration and forced migration, place of residence of local citizens and the attitude of rejection towards migrants.